Ultra-thin layer reactor and method for rapidly synthesizing submicron ZSM-5 zeolite
By adopting a solid-phase-like synthesis strategy in the ultra-thin sheet reactor, submicron ZSM-5 zeolites are rapidly synthesized, which solves the problems of high energy consumption, pollution and long synthesis cycles in traditional synthesis methods, and achieves efficient, environmentally friendly and low-cost preparation of ZSM-5 zeolites.
Patent Information
- Application Number
- CN202411832679.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The existing ZSM-5 zeolite synthesis methods have problems such as high energy consumption, harmful gas emissions, waste liquid generation and long synthesis cycles, and the design of traditional reactors limits heat transfer efficiency and experimental control.
The ultra-thin sheet reactor and solid-phase synthesis strategy were adopted to prepare geodesic polymers as silicon sources by pickling illite, and the aluminum and alkali sources were added at high temperatures, and the sub-micron ZSM-5 zeolite was quickly synthesized using the ultra-thin sheet reactor.
The heat transfer rate and experimental efficiency are significantly improved, the synthesis time is shortened to no more than 60 minutes, the production cost and environmental pollution are reduced, and the prepared ZSM-5 zeolite has high crystallinity and long-life catalytic properties.
Smart Images

Figure CN119281236B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of inorganic solid catalyst preparation, and in particular to an ultra-thin layer reactor and a method for rapidly synthesizing submicron ZSM-5 zeolite thereof. Background Art
[0002] ZSM-5 molecular sieve has broad application prospects in the fields of petrochemicals, environmental protection, pharmaceutical manufacturing and food processing due to its unique pore structure, high specific surface area and excellent thermal stability. With the improvement of environmental awareness and the advancement of industrial technology, the preparation process of ZSM-5 molecular sieve is constantly developing in the direction of green, environmental protection, high efficiency and low cost.
[0003] At present, most of the traditional ZSM-5 molecular sieves are synthesized in a hydrothermal system using quaternary ammonium cations or other organic amine molecular templates as structure-directing agents. However, the removal of organic templates in the later stage of synthesis will not only consume a lot of energy but also lead to the emission of a large amount of harmful gases. Moreover, since most of these methods are completed in a hydrothermal system, a large amount of waste liquid will be generated in industrial production and the synthesis yield is relatively low. In addition, the hydrothermal synthesis system involves complex physical and chemical changes and mass transfer and heat transfer processes, which have extremely strict requirements on the control of overall production conditions. Therefore, the high synthesis cost, inefficient synthesis process and environmental pollution problems that cannot be ignored have prompted people to innovate the synthesis method. With the popularization of environmentally friendly concepts and the growing development of atomic economic industries, it is extremely important to find a simple, efficient, economical and environmentally friendly strategy for the industrial preparation of hierarchical pore ZSM-5 zeolites.
[0004] Under template-free conditions, the solid-phase synthesis strategy is used to prepare monolithic ZSM-5 zeolite molecular sieves. Because it does not use templates and a large amount of solvents, it is regarded as a highly promising green synthesis route and has been popular among researchers in recent years. It is worth noting that although this method can synthesize ZSM-5 zeolite in a green way, compared with the synthesis process with the presence of organic templates, the template-free method is less likely to nucleate in the early stage of crystallization due to the lack of template induction, and thus requires higher nucleation activation energy and growth activation energy to drive the effective formation of zeolite crystals. However, the operating temperature of the hydrothermal reaction reactor currently used is generally limited to about 200°C, and it is usually operated in a polytetrafluoroethylene lined environment. Such a design not only makes the volume of the reactor very large, but also makes it inconvenient to control variables, and the experimental error is large. It is limited by the single design of the reactor body and cannot realize the parallel operation of multiple groups of experiments. In addition, the polytetrafluoroethylene lining is easy to induce a high-pressure environment, which affects the stable progress of the chemical reaction. More importantly, the heat transfer performance of polytetrafluoroethylene is relatively poor, and it is difficult to fully meet the high heat requirements of the reaction, especially in the case of zeolite crystal synthesis, which is temperature-sensitive and requires efficient heat exchange. This problem is particularly prominent, and it brings additional technical challenges to the effective synthesis of zeolite crystals. Therefore, how to optimize the synthesis strategy under template-free conditions and improve the heat transfer efficiency and reaction condition control of the reaction system has become a key issue that needs to be solved urgently. Summary of the invention
[0005] The present invention aims to provide an ultra-thin layer reactor to solve the problems of low heat transfer rate and inability to carry out multiple groups of experiments simultaneously in the same reactor.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] An ultra-thin layer reactor comprises a reactor body, wherein the outer wall of the reactor body is provided with a threaded ring, a plurality of external threads are bored on the threaded ring, the threaded ring is tightly connected with a reactor cover through the external threads thereon, a stainless steel upper gasket is provided inside the reactor cover, a cross-shaped stainless steel spacer is provided on the other side of the stainless steel upper gasket relative to the reactor cover, a stainless steel lower gasket is provided on the other side of the cross-shaped stainless steel spacer relative to the stainless steel upper gasket, a groove is provided on the stainless steel lower gasket near the cross-shaped stainless steel spacer, the cross-shaped stainless steel spacer and the stainless steel lower gasket are mutually clamped through the groove, the stainless steel lower gasket is a hollow cylinder, and a plurality of small holes are opened on the side of the stainless steel lower gasket near the cross-shaped stainless steel spacer.
[0008] Compared with the prior art, the present invention has the following advantages:
[0009] The ultra-thin layer reactor described in the present invention improves the experimental efficiency by setting a stainless steel spacer, and at the same time significantly improves the heat transfer rate. The use of the reactor to assist the solid-phase synthesis system to synthesize zeolite can realize a high-temperature strategy to shorten the synthesis time to no more than 60 minutes, thereby greatly improving the synthesis efficiency. In addition, the surface defect sites of the ZSM-5 crystal synthesized at high temperature are extremely small, which is conducive to its long-life catalytic reaction.
[0010] Another object of the present invention is to propose a method for rapidly synthesizing submicron ZSM-5 zeolite to solve the problems of long synthesis cycle and high synthesis cost caused by using a template-free method in the existing technology for synthesizing monolithic multi-level pore submicron ZSM-5 zeolite molecular sieves.
[0011] To achieve the above-mentioned purpose, the technical solution of the present invention is implemented as follows: a method for rapidly synthesizing submicron ZSM-5 zeolite, the method comprising: using geopolymer produced by acid-washing illite as a silicon source, adding an aluminum source and an alkali source, transferring it to an ultra-thin layer reactor for a high-temperature solid-phase reaction, so as to rapidly prepare an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0012] Furthermore, the specific steps of the illite rapid synthesis of monolithic multi-level pore submicron ZSM-5 zeolite are as follows:
[0013] Step 1, a process for preparing geopolymer by acid washing illite;
[0014] Step 1.1, the illite raw material ore is ball-milled and sieved to obtain illite powder with a particle size of less than 200 mesh;
[0015] Step 1.2, illite powder and 4 mol / L hydrochloric acid are mixed at a ratio of 1:7.5 g / mL and loaded into a hydrothermal reactor;
[0016] Step 1.3, placing the hydrothermal reactor in an oven and reacting at 170°C for 4 hours;
[0017] Step 1.4, after taking out the reactant, filter it, wash the reaction product with distilled water until it is neutral, place it in an oven at 80°C for 12 hours, and the obtained white powder is illite-based mineral polymer;
[0018] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0019] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min to 30 min;
[0020] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 25-45: 1: 0.14-0.19: 0-3.5, grind manually to make the material mix evenly;
[0021] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 300-400° C. for 15-60 minutes;
[0022] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0023] Furthermore, the aluminum source is aluminum sulfate or sodium aluminate.
[0024] Compared with the prior art, the invention has the following beneficial effects:
[0025] 1. The method of the present invention uses cheap illite resources as raw materials, which not only greatly reduces the production cost of ZSM-5 zeolite molecular sieve, but also cleverly utilizes the presence of a large number of structural units constituting clay structures in the geopolymer produced by depolymerizing illite, which makes it exhibit ultra-high chemical activity during the crystallization process into zeolite, promotes the rapid generation of ZSM-5 zeolite molecular sieve, thereby achieving a win-win situation in cost control and synthesis efficiency.
[0026] 2. In the present invention, organic amines and industrial crystal seeds are completely eliminated as structure-directing agents, thus avoiding environmental pollution caused by the use of organic matter in synthesis and reducing the synthesis cost.
[0027] 3. In the present invention, ZSM-5 zeolite molecular sieve is directly synthesized by a solid-phase method in an ultra-thin layer reactor, and only a small amount of solvent is needed, which not only avoids the discharge of a large amount of wastewater in production, but also reduces the pressure inside the reactor and improves the safety of the synthesis.
[0028] 4. The monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared by the present invention has high crystallinity and a grain size of about 800 nm. During the synthesis process, crystal accumulation will form intercrystalline voids inside the synthetic product, which will lead to a multi-level pore structure in the synthetic product, which is beneficial for it to be used as a high-life and long-acting solid acid catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0030] Figure 1Schematic diagram of an ultra-thin sheet reactor according to an embodiment of the present invention;
[0031] Figure 2 It is an overall schematic diagram of the ultra-thin layer reactor according to an embodiment of the present invention;
[0032] Figure 3 is an XRD curve diagram of ZSM-5 described in an embodiment of the present invention;
[0033] Figure 4 is a SEM image of the ZSM-5 sample described in the embodiment of the present invention;
[0034] Explanation of the accompanying drawings: 1. Reactor cover; 2. Stainless steel upper gasket; 3. Cross-shaped stainless steel spacer; 4. Stainless steel lower gasket; 5. Groove; 6. Small hole; 7. Reactor body; 8. Threaded ring. DETAILED DESCRIPTION
[0035] The following is a further detailed description of the embodiments of the invention in conjunction with the accompanying drawings and examples. The following examples are used to illustrate the invention but cannot be used to limit the scope of the invention.
[0036] Embodiment 1:
[0037] An ultra-thin layer reactor, such as Figure 1-2 As shown, it includes a reactor body 7, the outer wall of the reactor body 7 is provided with a thread ring 8, a plurality of external threads are drilled on the thread ring 8, the thread ring 8 is tightly connected with the reactor cover 1 through the external threads thereon, a stainless steel upper gasket 2 is provided in the reactor cover 1, a cross-shaped stainless steel spacer 3 is provided on the other side of the stainless steel upper gasket 2 relative to the reactor cover, a stainless steel lower gasket 4 is provided on the other side of the cross-shaped stainless steel spacer 3 relative to the stainless steel upper gasket, a groove 5 is provided on the stainless steel lower gasket 4 near the cross-shaped stainless steel spacer 3, the cross-shaped stainless steel spacer 3 and the stainless steel lower gasket 4 are mutually clamped through the groove 5, the stainless steel lower gasket 4 is a hollow cylinder, and a plurality of small holes 6 are opened on the stainless steel lower gasket 4 near the cross-shaped stainless steel spacer 3.
[0038] A method for rapidly synthesizing submicron ZSM-5 zeolite specifically comprises the following steps:
[0039] Step 1, a process for preparing geopolymer by acid washing illite;
[0040] Step 1.1, the illite raw material ore is ball-milled and sieved to obtain illite powder with a particle size of less than 200 mesh;
[0041] Step 1.2, illite powder and 4 mol / L hydrochloric acid are mixed at a ratio of 1:7.5 g / mL and loaded into a hydrothermal reactor;
[0042] Step 1.3, placing the hydrothermal reactor in an oven and reacting at 170°C for 4 hours;
[0043] Step 1.4, after taking out the reactant, filter it, wash the reaction product with distilled water until it is neutral, place it in an oven at 80°C for 12 hours, and the obtained white powder is illite-based mineral polymer;
[0044] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0045] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0046] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 30:1:0.14:1, and grind manually to make the materials evenly mixed;
[0047] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 400° C. for 30 min;
[0048] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0049] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 1; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in a in .
[0050] Embodiment 2:
[0051] Step 1, process for preparing geopolymer by acid washing illite: same as in Example 1
[0052] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0053] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0054] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 30: 1: 0.14: 3.5, and grind manually to make the materials evenly mixed;
[0055] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 400° C. for 30 min;
[0056] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0057] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 2; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in b.
[0058] Embodiment 3:
[0059] Step 1, process for preparing geopolymer by acid washing illite: same as in Example 1
[0060] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0061] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0062] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 40: 1: 0.14: 3.5, and grind manually to make the materials evenly mixed;
[0063] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 400° C. for 30 min;
[0064] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0065] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 3; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in c.
[0066] Embodiment 4:
[0067] Step 1, process for preparing geopolymer by acid washing illite: same as in Example 1
[0068] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0069] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0070] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 30: 1: 0.19: 3.5, and grind manually to make the materials evenly mixed;
[0071] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 300° C. for 30 min;
[0072] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0073] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 4; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in d.
[0074] Embodiment 5:
[0075] Step 1, process for preparing geopolymer by acid washing illite: same as in Example 1
[0076] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0077] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0078] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 30: 1: 0.19: 3.5, and grind manually to make the materials evenly mixed;
[0079] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 400° C. for 15 min;
[0080] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0081] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 5; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in e.
[0082] Embodiment 6:
[0083] Step 1, process for preparing geopolymer by acid washing illite: same as in Example 1
[0084] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0085] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0086] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 30: 1: 0.19: 3.5, and grind manually to make the materials evenly mixed;
[0087] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 350° C. for 30 min;
[0088] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0089] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 6; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in f.
[0090] Embodiment 7:
[0091] Step 1, process for preparing geopolymer by acid washing illite: same as in Example 1
[0092] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0093] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0094] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 30: 1: 0.19: 3.5, and grind manually to make the materials evenly mixed;
[0095] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 350° C. for 60 min;
[0096] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0097] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 7; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in g.
[0098] Embodiment 8:
[0099] Step 1, process for preparing geopolymer by acid washing illite: same as in Example 1
[0100] Step 2, a process for monolithic multi-level pore submicron ZSM-5 zeolite;
[0101] Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min;
[0102] Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 30: 1: 0.19: 3.5, and grind manually to make the materials evenly mixed;
[0103] Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 300° C. for 60 min;
[0104] Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
[0105] Specifically, the XRD curve of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve prepared in this embodiment is as follows: Figure 3 8; The SEM image of the monolithic multi-level pore submicron ZSM-5 zeolite molecular sieve sample prepared in this embodiment is as shown in Figure 4 As shown in h.
[0106] Serial number name Raw material ratio Relative crystallinity (%) 1 Example 1 <![CDATA[SiO2:Al2O3:NaOH:H2O = 30:1:0.14:1 Reaction time: 30 min; Reaction temperature: 400 °C]]> 60 2 Example 2 <![CDATA[SiO2:Al2O3:NaOH:H2O = 30:1:0.14:3.5 Reaction time: 30 min; Reaction temperature: 400 °C]]> 75 3 Example 3 <![CDATA[SiO2:Al2O3:NaOH:H2O = 45:1:0.14:3.5 Reaction time: 30 min; Reaction temperature: 400 °C]]> 94 4 Example 4 <![CDATA[SiO2:Al2O3:NaOH:H2O = 30:1:0.19:3.5 Reaction time: 30 min; Reaction temperature: 300 °C]]> 96 5 Example 5 <![CDATA[SiO2:Al2O3:NaOH:H2O = 30:1:0.19:3.5 Reaction time 15 min; Reaction temperature: 400 °C]]> 128 6 Example 6 <![CDATA[SiO2:Al2O3:NaOH:H2O = 30:1:0.19:3.5 Reaction time: 30 min; Reaction temperature: 350 °C]]> 125 7 Example 7 <![CDATA[SiO2:Al2O3:NaOH:H2O = 30:1:0.19:3.5 Reaction time 60 min; Reaction temperature: 350 °C]]> 115 8 Example 8 <![CDATA[SiO2:Al2O3:NaOH:H2O = 30:1:0.19:3.5 Reaction time: 60 min; Reaction temperature: 300 °C]]> 120
[0107] The table shows the crystallinity evaluation of the zeolite molecular sieve prepared in each embodiment, using an X-ray powder diffractometer (XRD, Aeris, PANalytical) using a Cu Kα radiation source, with a 2θ range of 5°-50° and an angular step of 0.02°. The relative crystallinity (RC) is calculated according to the method described by Gulfaz and Sand. Wherein, X is the peak surface of the solid product and the reference sample in the 2θ range of 22°-25°, and Y is the peak surface of the zeolite molecular sieve sold on the market (Nankai University, silicon-aluminum ratio 40) in the 2θ range of 22°-25°.
[0108]
[0109] The example SiO2 in the table is actually an illite-based mineral polymer. The acid is hydrochloric acid. When the acid used in the reaction is sulfuric acid or other strong acids, an illite-based mesoporous silica product can also be obtained. In addition, those skilled in the art have the ability to replace the illite in the present invention with other natural silicate minerals to achieve the same technical effect (such as kaolin, montmorillonite, diatomaceous earth, etc.), which should also be regarded as the scope of rights covered by the present invention. The above is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.
Claims
1. An ultra-thin layer reactor, characterized in that: The invention comprises a reactor body (7), wherein the outer wall of the reactor body (7) is provided with a thread ring (8), the thread ring (8) is provided with a plurality of external threads, the thread ring (8) is threadedly connected to a reactor cover (1) via the external threads thereon, a stainless steel upper gasket (2) is provided inside the reactor cover (1), a cross-shaped stainless steel spacer (3) is provided on the other side of the stainless steel upper gasket (2) relative to the reactor cover (1), a stainless steel lower gasket (4) is provided on the other side of the cross-shaped stainless steel spacer (3) relative to the stainless steel upper gasket (2), a groove (5) is provided on the stainless steel lower gasket (4) near the cross-shaped stainless steel spacer (3), the cross-shaped stainless steel spacer (3) and the stainless steel lower gasket (4) are mutually clamped via the groove (5), the stainless steel lower gasket (4) is a hollow cylinder, and a plurality of small holes (6) are provided on the side of the stainless steel lower gasket (4) near the cross-shaped stainless steel spacer (3).
2. A method for rapidly synthesizing submicron ZSM-5 zeolite, characterized in that: The ultra-thin laminar reactor protected by claim 1 is used, and the method is as follows: using the geopolymer produced by acid-washing illite as a silicon source, adding an aluminum source and an alkali source, transferring it to an ultra-thin laminar reactor for a high-temperature solid-phase reaction, so as to quickly prepare an integral multi-level pore submicron ZSM-5 zeolite molecular sieve; The specific steps of the illite rapid synthesis of monolithic multi-level pore submicron ZSM-5 zeolite are as follows: Step 1, a process for preparing geopolymer by acid washing illite; Step 1.1, the illite raw material ore is ball-milled and sieved to obtain illite powder with a particle size of less than 200 mesh; Step 1.2, illite powder and 4 mol / L hydrochloric acid are mixed at a ratio of 1:7.5 g / mL and loaded into a hydrothermal reactor; Step 1.3, placing the hydrothermal reactor in an oven and reacting at 170°C for 4 hours; Step 1.4, after taking out the reactant, filter it, wash the reaction product with distilled water until it is neutral, place it in an oven at 80°C for 12 hours, and the obtained white powder is illite-based mineral polymer; Step 2, a synthesis process of monolithic multi-level pore submicron ZSM-5 zeolite; Step 2.1, grinding illite-based mineral polymer and alkali source in a mortar for 10 min to 30 min; Step 2.2, add distilled water to make the material molar ratio: illite-based mineral polymer (SiO2): Al2O3: NaOH: H2O = 25-45: 1: 0.14-0.19: 0-3.5, and grind manually to mix the materials evenly; Step 3, transferring the mixed material to an ultra-thin layer reactor and crystallizing at 300-400° C. for 15 min to 60 min; Step 4, taking out the ultra-thin layer reactor, waiting for its temperature to drop to room temperature, centrifuging and drying the reaction product to obtain an integral multi-level pore submicron ZSM-5 zeolite molecular sieve.
3. The method for rapidly synthesizing submicron ZSM-5 zeolite according to claim 2, characterized in that: The aluminum source is aluminum sulfate or sodium aluminate.
Citation Information
Patent Citations
Template-free method for synthesizing hierarchical pore ZSM-5 zeolite molecular sieve from illite
CN109336129A